Characteristics of the atmospheric particle formation events observed at a borel forest site in southern Finland - Mäkelä, J. M.; Dal Maso, M.; Pirjola, L.; Keronen, P.; Laakso, L.; Kulmala, M.; Laaksonen, A. (Boreal Environment Research Publishing Board, 2024)
We analysed 184 formation events of new atmospheric aerosol particles, observed at a boreal forest site in Hyytiälä, southern Finland. Recognition, selection and classification of the formation events was based on continuous experimental size distribution data for submicron particles from a period 31 January 1996–18 September 1999 (1327 days). The formation events were classified, and their characteristic features such as the starting time and duration of the particle formation, the number of new particles produced, the particle growth rate at the beginning of the formation burst, and the final particle size after the observed 8-hour growth subsequent to formation, were quantified. The formation rate of 3 nm particles, J3, varied in the range 0.001–1 particles cm–3 s–1. The ultrafine particle growth rates varied in the range 1–17 nm h–1. The possible coupling between the apparent formation rate of new particles and their growth rate subsequent to formation was discussed.